Niños e infantes con necesidad y lamento. ¿Por qué no aplicar el tratamiento? - Holguin Alvarez, Jhon (2014)
The author develops a constructive criticism of existing descriptive evaluation opposite to experimental method as a mean of treatment of analyzed variables in the Peruvian context. In turn, different aspects are discovered of the Peruvian reality in university and educational institutions of EBR (Regular Basic Education) students, as part of educational problem and of research from professional academic training and teaching practice.